2019
DOI: 10.1155/2019/3920414
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Water-Inrush Risk Based on Permeability Evolution in Coal Mine and Backfill Prevention Discussion

Abstract: Induced by coal mining, the fractures constantly occur in geologic strata until failure occurs, which provide channels for water flow. Therefore, it is essential to investigate the permeability evolution of rocks under load. Borehole sampling was conducted in a bedrock layer beneath an aquifer, and the permeability evolution of sandstone specimens under different confining pressures was tested in rock mechanics testing laboratories. The results indicated that the permeability gradually decreases with the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…A large number of experiments have shown that water-inrush or coal and gas outburst accidents caused by seepage loss in mining projects are often caused by sudden changes in the seepage parameters. erefore, a dynamic method should be used to study the non-Darcy seepage differential dynamic system of fractured coal rock [34][35][36]. For one-dimensional (1D) passive flow, the 1D non-Darcy seepage dynamics equations of fractured coal rock can be expressed as…”
Section: Estimate Of Seepage Loss Stabilitymentioning
confidence: 99%
“…A large number of experiments have shown that water-inrush or coal and gas outburst accidents caused by seepage loss in mining projects are often caused by sudden changes in the seepage parameters. erefore, a dynamic method should be used to study the non-Darcy seepage differential dynamic system of fractured coal rock [34][35][36]. For one-dimensional (1D) passive flow, the 1D non-Darcy seepage dynamics equations of fractured coal rock can be expressed as…”
Section: Estimate Of Seepage Loss Stabilitymentioning
confidence: 99%
“…This technology can control the depth of the bottom plate damage and can play a better role in groundwater resources [27][28][29][30]. The protective effect of the coal mine, especially under the condition of coal mining under confined water, can significantly improve the safe production conditions of coal mines [31][32][33][34]. Furthermore, this technology can effectively control the surface subsidence and deformation to achieve nonrelocation of coal mining, which can greatly improve coal resources.…”
Section: Introductionmentioning
confidence: 99%